Pengelolaan manajemen keselamatan kerja pada divisi sarana dan prasarana LLP-KUKM (Smesco Indonesia) - Abdullah, Ismail; Zuraida, Rida (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
The high number of work accidents in building maintenance is a serious concern for the whole community and the government. So that learning for the community about work accidents is getting higher, thereby encouraging public awareness of the application of occupational safety and health management which is something that must be understood by workers in order to minimize the risk of work accidents occurring in the work environment. This study aims to evaluate the standard operating procedures (SOP) used in the facilities and infrastructure division of the Smesco Indonesia Marketing-Cooperative and Small and Medium Enterprises Service Institute (LLP-KUKM). The data collection method used in this research is interview analysis of building maintenance operators, as well as direct field observations. Followed by evaluation of observational data and interviews supporting data. The results of interviews with operators are in the form of secondary data and primary data. Primary data were obtained from direct field observations and interviews with operators. While secondary data is obtained from the organizational structure, standard procedures, regulations in the field and personal protective equipment (PPE). The next step is to analyze these data by compiling, discussing and evaluating these data. Where the final result of this study is to explain the application accompanied by supervision of occupational safety and health. Other impacts can also create work effectiveness.